2013
DOI: 10.1088/2041-8205/773/1/l13
|View full text |Cite
|
Sign up to set email alerts
|

Keck Observations of the Galactic Center Source G2: Gas Cloud or Star?

Abstract: We present new observations and analysis of G2 -the intriguing red emission-line object which is quickly approaching the Galaxy's central black hole. The observations were obtained with the laser guide star adaptive optics systems on the W. M. Keck I and II telescopes and include spectroscopy (R ∼ 3600) centered on the Hydrogen Brγ line as well as K ′ (2.1 µm) and L ′ (3.8 µm) imaging. Analysis of these observations shows the Br-γ line emission has a positional offset from the L ′ continuum. This offset is lik… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
143
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(148 citation statements)
references
References 46 publications
5
143
0
Order By: Relevance
“…In this paper, the primary data sets are WMKO images that have been acquired through the L′ (λ 0 =3.8 μm) broadband filter over a 13 yr period with NIRC2, the facility near-infrared camera (PI: K. Matthews) fed by the Keck II laser guide star adaptive optics system (LGSAO; van Dam et al 2006;Wizinowich et al 2006). Ten of the 12 epochs have been previously reported by us and are part of our group's archive of fully calibrated data sets (Ghez et al 2004(Ghez et al , 2005bHornstein et al 2007;Phifer et al 2013;Witzel et al 2014). Two additional epochs of observation, 2013 August and 2016 May, are reported here for the first time.…”
Section: Data Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, the primary data sets are WMKO images that have been acquired through the L′ (λ 0 =3.8 μm) broadband filter over a 13 yr period with NIRC2, the facility near-infrared camera (PI: K. Matthews) fed by the Keck II laser guide star adaptive optics system (LGSAO; van Dam et al 2006;Wizinowich et al 2006). Ten of the 12 epochs have been previously reported by us and are part of our group's archive of fully calibrated data sets (Ghez et al 2004(Ghez et al , 2005bHornstein et al 2007;Phifer et al 2013;Witzel et al 2014). Two additional epochs of observation, 2013 August and 2016 May, are reported here for the first time.…”
Section: Data Setsmentioning
confidence: 99%
“…The new L′ data sets were observed and calibrated using the same techniques described in the papers reporting our other L′ data sets (Stolte et al 2010;Phifer et al 2013;Witzel et al 2014). This followed standard techniques with the exception of the treatment of the sky exposures, which were taken for each field rotator mirror position within the same range as the science data in steps of ∼2°.…”
Section: Data Setsmentioning
confidence: 99%
“…The tidal disruption of this cloud is being monitored by different groups (e.g., Eckart et al 2013;Gillessen et al 2013;Phifer et al 2013) and provides a unique opportunity to test accretion physics, due to both its proximity and the timescale on which it happens. Gillessen et al (2012) estimated the mass of G2 to be ∼ 3 M⊕ from its line emission.…”
Section: Introductionmentioning
confidence: 99%
“…The second possibility under discussion is that G2 is a circumstellar cloud around a star that provides stabilizing gravity and continuously replenishes the gas. Studies supporting this scenario highlighted that the tail might only be a fore-or background feature and might not be physically connected to G2 (Phifer et al 2013;Valencia et al 2015). Recent observations have also shown that G2 survived its pericenter passage as a compact source, which might be a clue that G2 is a star enshrouded by gas and/or dust (Witzel et al 2014;Valencia et al 2015).…”
Section: Introductionmentioning
confidence: 99%